Care for all at the end of life. Issue 7650 (8th April 2008) - Murray, Scott A; Sheikh, Aziz
Abstract : Scott Murray and Aziz Sheikh say that the lessons learnt from palliative care for cancer need to be applied to other fatal conditions. Healthcare delivery that is tailored to the varying needs of patients with these diseases will be crucial in making a difference, says Joanne Lynn (doi: 10.1136/bmj.39535.656319.94 )